Definitions and criteria for diabetic foot disease. (14th January 2020) - van Netten, Jaap J.; Bus, Sicco A.; Apelqvist, Jan; Lipsky, Benjamin A.; Hinchliffe, Robert J.; Game, Frances; Rayman, Gerry; Lazzarini, Peter A.; Forsythe, Rachael O.; Peters, Edgar J.G.; Senneville, Éric; Vas, Prashanth; et al.
Abstract: Multiple disciplines are involved in the management of diabetic foot disease, and a common vocabulary is essential for clear communication. Based on the systematic reviews of the literature that form the basis of the International Working Group on the Diabetic Foot (IWGDF) Guidelines, the IWGDF has developed a set of definitions and criteria for diabetic foot disease. This document describes these definitions and criteria. We suggest these definitions be used consistently in both clinical practice and research to facilitate clear communication between professionals.